The Digitized First Byurakan Survey Database Late-Type Stars Candidates. New Confirmations. II - Gigoyan, K. K.; Gigoyan, K. S.; Sarkissian, A.; Meftah, M.; Bekki, S.; Karapetyan, E.; Rahmatullaeva, F.; Kostandyan, G. R.
Three new carbon C stars was confirmed among the sample of the Late-Type Stars candidates, selected on the Digitized First Byurakan Survey (DFBS) spectral plates. The DFBS is the digitized version of the First Byurakan Survey (FBS, or Markarian survey). The FBS was the first systematic survey of the extragalactic sky. This objective-prism survey was carried out in 1965-1980 by B.E.Markarian and his colleagues using the 1 m Schmidt telescope of the Byurakan Astrophysical Observatory and resulted in discovery of 1517 UV-excess (Markarian) galaxies. FBS spectral plates have been used long period to search and study faint LTS (C-type and M-type stars) at high Galactic latitudes. In this work we present Gaia DR3 photometric data, spectra, light curves, distances, high above/below Galactic plane, radial velocities (RV), and other important physical characteristics from the modern astronomical catalogues for three new confirmed DFBS C stars. The confirmation is based on Gaia DR3 BP/RP low-resolution spectral database. In our previous studies of the DFBS plates, these objects were presented as LTS candidates. One of the new confirmed objects is N-type C star, which is a Mira-type variable. Two remaining objects, are early CH-type giants at high Galactic latitudes. Most probably they present binary systems. Три новые углеродные С звезды были подтверждены среди кандидатов звезд поздних спектральных классов, отобранных на оцифрованных пластинках Первого Бюраканского Обзора (DFBS). DFBS - это оцифрованная версия Первого Бюраканского Обзора (FBS) или Маркаряновского обзора. FBS является первым систематическим внегалактическим обзором. Он был осуществлен Маркаряном и его коллегами в 1965-1980гг. с объективной призмой с использованием 1-м телескопа Шмидта Бюраканской астрофизической обсерватории (БАО) и увенчался открытием 1517 галактик с UV- избытком, названных галактиками Маркаряна. Пластинки обзора FBS длительное время использовались для поиска и изучения слабых звезд поздних спектральных типов (LTS, M и С (углеродные)) на высоких галактических широтах. В данной работе мы приводим Gaia DR3 фотометрические данные, спектры, кривые блеска, расстояния, радиальные скорости (RV) и другие важные физические характеристики из современных астрономических каталогов для трех новых DFBS C звезд. Подтверждение основано на Gaia DR3 BP/RP спектральных базах данных. В наших предыдущих исследованиях эти объекты были представлены как кандидаты в LTS. Oдним из новых подтвержденных объектов, это C звезда типа N. Два оставшихся объекта являются CH гигантами в высоких галактических широтах. Скорее всего, они представляют двойные системы.
Keywords: Astrophysics